Four new species of the genus Phlugiolopsis (Orthoptera: Tettigoniidae: Meconematinae) from Western Yunnan, China - Yao, Yuqing; Bian, Xun; Zhang, Bin (Zootaxa, 2025)
A comprehensive list of species of the genus Phlugiolopsis is presented. In addition, four new species, Phlugiolopsis conica sp. nov., Phlugiolopsis gongshanensis sp. nov., Phlugiolopsis longicaudata sp. nov. and Phlugiolopsis placentis sp. nov., from Yunnan, China, are described and illustrated. To distinguish with Ph. longicaudata sp. nov., we provided the morphological illustrations of Ph. montana Wang, Li & Liu, 2012. All specimens were deposited in Guangxi Normal University.